ESL teachers’ perceptions and practices of code-switching in a Malaysian Chinese independent secondary school - Wong, Yeevon; Yoong, David (Journal of Modern Languages, 2019)
Code-switching (CS) is one of the communicative strategies used in defining and structuring social relationships of speakers. In this study, we demonstrate how teachers perceive and employ CS in a Malaysian Chinese Independent School (MCIS) English classrooms to achieve communicative intents and to create a sense of belonging among students. Ethnography recording of classroom discourse and semi-structured interviews with seven English teachers were employed. The analysis reveals a noteworthy commitment that CS does not only act as a pedagogical tool but also as a means of facilitating interpersonal communication in class.